On the Effect of Hot Isostatic Pressing on the Creep Life of a Single Crystal Superalloys1 . Issue 8 (4th April 2016) - Mujica Roncery, Lais; Lopez‐Galilea, Inmaculada; Ruttert, Benjamin; Bürger, David; Wollgramm, Philip; Eggeler, Gunther; Theisen, Werner
Abstract : The creep behavior of a single‐crystal Ni‐base superalloy in two microstructural states is compared. One is obtained by casting followed by a conventional heat treatment. The other results from the same nominal heat treatment integrated into a hot isostatic pressing process. The microstructure after HIP differed from that in the conventional route in two respects. First, the γ′ particles are smaller and the γ channels are narrower. Second, after HIP, the number density of pores is lower and the pore sizes are smaller. The HIP microstructure improves creep in two respects: the finer γ/γ′‐microstructure results in lower minimum creep rates. Moreover, the shrinkage of cast porosity during HIP delays the nucleation and growth of micro cracks and results in higher rupture strains in the low‐temperature high stress regime. Abstract : In the present work the authors compare the creep behavior of a single crystal Ni‐base superalloy in two microstructural states, with and without HIP. The HIP process improves creep in two respects: the finer γ/γ'‐microstructure results in lower minimum creep rates and the shrinkage of cast porosity during HIP results in higher rupture strains in the low temperature high stress regime.